ANALYSIS TESTING WEBSITE NEW INSTALLATION PLN ELECTRICITY USING BOUNDARY VALUE ANALYSIS AND FUNCTIONAL TESTING - Rasmila; Dwi Angga Apriansyah (Fakultas Teknik Universitas Lambung Mangkurat, 2022)
The website contains a lot of information and data that must protect. Input and output aspects of communication have a significant role in a service website to provide accurate information and avoid misinformation due to an imperfect system. Various system tests have been tried to identify the advantages and disadvantages of a web-based data system. This study uses a black box checking out procedure. In black field checking out, there are several testing techniques. This check uses boundary value analysis and functional testing. The boundary value analysis method plays tests based on the most suitable and minimum variety of digits to create fair and invalid values. The early tiers of this test are figuring out the functionality of the shape to be processed and ensuring the most excellent and minimum range of entering characters. The consequences of this research are in the form of records containing the harm to the device so that machine managers can improve the machine's quality in serving users or customers.